Descriptive and functional anatomy of the Heschl Gyrus: historical review, manual labelling and current perspectives. - Henderson, Douglas; Bichoutar, Ihsane; Moxham, Bernard; Faidherbe, Virginie; Plaisant, Odile; Guédon, Alexis (Surgical & Radiologic Anatomy, 2023)
Purpose: The Heschl Gyrus (HG), which includes the Primary Auditory Cortex (PAC), lies on the upper surface of the superior temporal gyrus (T1). It has been the subject of growing interest in the fields of neuroscience over the past decade. Given the considerable interhemispheric and interindividual variability of its morphology, manual labelling remains the gold standard for its radio-anatomical study. The aim of this study was to revisit the original work of Richard L. Heschl, to provide a broad overview of the available anatomical knowledge and to propose a manually labelled 3D digital model. Methods: We reviewed existing works on the HG, from Heschl's original publication of 1878, Dejerine neuroanatomical atlas of 1895 to the most recent digital atlases (Julich-Brain Cytoarchitectonic Atlas, the Human Connectome Project). Our segmentation work was based on data from the BigBrain Project and used the MRIcron 2019 software. Results: The original publication by Heschl has been translated into French and English. We propose a correspondence of previous nomenclatures with the most recent ones, including the Terminologia Neuroanatomica. Finally, despite the notable anatomical variability of the HG, clear and coherent segmentation criteria allowed us to generate a 3D digital model of the HG. Discussion and conclusion: Heschl's work is still relevant and could impulse further anatomical and functional studies. The segmentation criteria could serve as a reference for manual labelling of the HG. Furthermore, a thorough, and historically based understanding of the morphological, microstructural and functional characteristics of the HG could be useful for manual segmentation.